Bulgaria - Ex-post impact assessment of the act on limiting administrative regulation and administration control on economic activity - World Bank (World Bank, 2012)
The ex-post impact assessment of the Limiting Administrative Regulation and Administrative Control on Economic Activity Act (LARACEAA) is part of the World Bank's support to the Government of Bulgaria through on-going analytical and advisory work in the area of regulatory reform. The purpose of the present ex-post impact assessment of the LARACEAA is to: (i) assess how the Act has been enforced, (ii) identify and estimate the impacts of the Act, and (iii) provide recommendations for amendments to the Act. Chapter one emphasizes the importance of the Act as part of the Bulgarian Government's role in advancing regulatory reform and improving the business environment; gives the scope of the assessment and presents the sources of information utilized; and delineates general limitations of the analysis. Chapter two outlines a policy framework by discussing coherence with the Governmental and European Union (EU) policies, as well as touching upon relevant documents on regulatory reform, followed by analysis of the goal and objectives of the Act, and identification of performance indicators for the measurement of the impact of the Act. Chapter three depicts the results of the ex-post impact assessment, while the final chapter four identifies the main problem; discusses underlying drivers and effects of the problem; and proposes recommendations for amendments to the Act.